2002
DOI: 10.12921/cmst.2002.08.01.17-30
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Interval Multistep Methods for Solving the Initial Value Problem

Abstract: Implicit interval methods of Adams-Moulton type for solving the initial value problem are proposed. It is proved that the exact solution of the problem belongs to interval-solutions obtained by the considered methods. Furthermore, the widths of interval-solutions are estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…In [18,20,26,28], we have proved that the exact solution of the initial value problem (1) belongs to the interval solutions Y k obtained by the implicit interval multistep methods considered in this section. In the same papers, we have estimated the widths of these solutions.…”
Section: As Previously Let Us Denote By T and Y The Sets In Which Thmentioning
confidence: 90%
See 1 more Smart Citation
“…In [18,20,26,28], we have proved that the exact solution of the initial value problem (1) belongs to the interval solutions Y k obtained by the implicit interval multistep methods considered in this section. In the same papers, we have estimated the widths of these solutions.…”
Section: As Previously Let Us Denote By T and Y The Sets In Which Thmentioning
confidence: 90%
“…Unfortunately, it can be shown that his formula fails in the simplest case, but it can be easily corrected [19,28]. Other explicit interval multistep methods have been considered in [26][27][28] and implicit ones in [18,20,[26][27][28]. In recent years, many studies have been conducted on a variety of interval methods based on high-order Taylor series (see, e.g., [2-4, 7, 17, 22, 36, 38, 40]).…”
Section: Introductionmentioning
confidence: 99%
“…Let the assumptions about F(T,Y) and Ψ(T,Y) be the same as in [1] and [2], Moreover let us assume that for i = 1, 2,..., k -1 are and the intervals Y i such as known. We can obtain such Y i by applying interval one-step method, for example an interval method of Runge-Kutta type (see [19] or [20]).…”
Section: ) ψ(T Y) -An Interval Extension Of ψ(T Y)mentioning
confidence: 99%
“…In our previous paper [1] we have considered implicit interval multistep methods of AdamsMoulton type for solving the initial value problem. On the basis of these methods and the explicit ones introduced by Sokin [2] we wanted to construct predictor-corrector (explicit-implicit) interval methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation